Tingkat Kepatuhan Wajib Pajak dengan Kesadaran Wajib Pajak sebagai Variabel Moderasi - Rinanto, Eka; Furkan, Lalu Muhammad; Hidayati, Siti Aisyah (E-Jurnal Akuntansi; Vol 32 No 11 (2022), 2022)
The study was conducted to analyze the effect of tax authorities' services and taxpayer knowledge on compliance with the level of taxpayer compliance with taxpayer awareness as a moderating variable in Mataram City during the Covid 19 pandemic. The study population was taxpayers registered at KPP Mataram Barat. The number of samples is 100 people with accidental sampling method. This research is a quantitative study with data processing methods using IBM SPSS Statistics 24. The results show that tax authorities have an effect on the level of taxpayer compliance, knowledge of the taxpayer has no effect on the level of taxpayer compliance. This research uses the moderating variable of taxpayer awareness to see the interaction between tax authorities and taxpayer knowledge variables. The results show that the interaction of taxpayer awareness is not able to moderate the relationship between tax authorities and taxpayer compliance, while the interaction of taxpayer awareness is able to moderate the knowledge of taxpayers on the level of taxpayer compliance. Keywords: Fiscal Service; Taxpayer Knowledge; Taxpayer Compliance; Taxpayer Awareness; Moderating Variable